Approved budget 1989; 1991; 2000; 2001 : Government of the Plateau State of Nigeria - Plateau State of Nigeria (Plateau Nigeria : Plateau State Government, 1989)
This book provides a detailed financial reports of the Plateau State Government with inclusion of the budgetary allocation to various ministries and agencies for the year 1989.
asm; 10/04/19
Loans
Keywords: Budget; Expenditures, public; Plateau State- Nigeria